2020
DOI: 10.6007/ijarbss/v10-i5/7171
|View full text |Cite
|
Sign up to set email alerts
|

Digital Literacy, Business Uncertainty & Economic Performance: An Empirical Study of Small Businesses in Sri Lanka

Abstract: The study attempts to investigate empirically how Digital Literacy (DL) affects the Business Uncertainty and Economic Performance particularly Small Enterprises (SEs) in Sri Lankan. The data were collected from 110 owners of SEs, conducting face to face interviews and analysed using Partial Least Squares-Structural Equation Modelling. The results discovered that the different dimensions of DL have a negative impact on business uncertainty and positive effects on the economic performance of SEs. Thus, the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 61 publications
2
16
0
2
Order By: Relevance
“…A study conducted by (RVSPK et al, 2020) showed that digital literacy does not significantly affect the performance of SMEs in Sri Lanka. This research revealed that business uncertainty plays the most dominant role in the relationship between digital literacy and performance.…”
Section: Hypothesis 1 (H 1 ): the Use Of Digital Technology Has An Im...mentioning
confidence: 99%
“…A study conducted by (RVSPK et al, 2020) showed that digital literacy does not significantly affect the performance of SMEs in Sri Lanka. This research revealed that business uncertainty plays the most dominant role in the relationship between digital literacy and performance.…”
Section: Hypothesis 1 (H 1 ): the Use Of Digital Technology Has An Im...mentioning
confidence: 99%
“…Menurut Keh et al (2007) menyatakan bahwa beberapa faktor yang perlu untuk diberi perhatian khusus oleh UMKM yaitu 1) kewirausahaan, 2) pemindaian dan pemantauan lingkungan, 3) mencari informasi yang dapat membantu memenuhi kebutuhan pelanggan agar dapat mengelola pengambilan risiko serta tantangan pesaing, 4) penelitian pasar untuk mendapatkan informasi tentang pangsa pasar. Berbeda dengan Rvspk et al (2020) menyatakan bahwa faktor-faktor yang harus diperhatikan oleh UMKM antara lain faktor keuangan dan faktor lingkungan. Namun, kekurangan kinerja UMKM di negara berkembang adalah kurangnya keahlian manajerial, orientasi pasar yang buruk, kurangnya keterampilan dan pengalaman, motivasi kewirausahaan yang rendah, penerapan manajemen lemah, terbatasnya sumber daya, dan penerapan teknologi yang masih rendah (Chakraborty et al, 2019).…”
Section: Pendahuluanunclassified
“…Terdapat beberapa variabel instrumental yang peneliti pertimbangkan untuk digunakan dalam penelitian ini karena sudah pernah dijadikan sebagai variabel pengukuran digitalisasi pada peneletian sebelumnya. Variabel-variabel tersebut adalah sumber daya manusia (ILD) (RVSPK et al, 2020), penggunaan ICT (PTIK) (Evangelista et al, 2014;Van Ark, 2015;Stanley et al, 2018;Adeleye & Eboagu, 2019;Irawan, 2013;Stancovic et al, 2021;Toader et al, 2018), kewirausahaan dan produktivitas (KP) (Srivastava et al, 2010), infrastruktur (IF) (Sahoo et al, 2012;Szymańska & Biegańska, 2012;Batuo, 2015;Mohanty & Bhanumurthy, 2019), dan keuangan (IIK) (Van et al, 2021;Levine, 2005;Goyal et al, 2004) di provinsi i pada waktu t. Data untuk kelima variabel ini tersedia di dalam komponen penyusun indeks EV-DCI sehingga peneliti dapat menggunakan metode Two-Stage Least Squares (2SLS) panel data dengan model sebagai berikut:…”
Section: Model Ekonometrikaunclassified